Severe Vitamin A Deficiency After Biliopancreatic Diversion - Lauren M. Lemieux MD; Vijaya Surampudi MD (SAGE Publishing, 2019)
Biliopancreatic diversion is a surgical procedure that causes weight loss via volume restriction and malabsorption. It is now rarely performed due to the risk of severe nutritional deficiencies including vitamin A. We report a case of severe vitamin A deficiency due to malabsorption from a biliopancreatic diversion procedure for weight loss. By the time the patient presented to our department, she had developed blindness refractory to parenteral vitamin A treatment. A unique feature of her case is the development of a rash with vitamin A injections. This reaction has only been reported in one case series of 3 patients in the published literature. Her case highlights the importance of vitamin deficiency screening in patients after bariatric surgery, and her skin reaction to the injections is a unique side effect that is not frequently observed.